Evocation of Trade Disputes Through Arbitration of The World Trade Organization - Herryani, Mas Rara Tri Retno; Rahma, Iklima Nur; Albar, Mohammad Haris Yusuf (Dinasti Research, 2025)
Arbitration is an independent, final and binding mechanism for resolving international commercial disputes within the framework of the WTO. There are two major international agreements on arbitration, namely the New York Convention and the ICSD Convention/Washington, which contains provisions in the form of